THE DESCRIPTIVE ANALYSIS OF HERDING ON JAKARTA ISLAMIC INDEX - Hazar Ihza Fauziah; Sylva Alif Rusmita (Universitas Airlangga, 2020)
Herding is irrational investor behavior, because investors do not make investment decisions based on economic fundamentals, but based on other investors in the same condition, or following market consensus. Herding is measured by looking at the relationship between return market portfolio and Cross-Sectional Absolute Deviation (CSAD). This study used quantile regression to measure herding behavior. The result shows that there is no indication of herding behavior in JII, which means that investors tend to behave rationally in making investment decisions. Keywords: CSAD, Herding Behavior, Quantile RegressionREFFERENCE Ahsan, A.F.M Mainul, Sarkar, Ahasan H. (2013). Herding in Dhaka stock exchange. Journal of Applied Business and Economics, 14(2), 11-19.Bikchandani, S. & Sharma, S. (2001). Herd behavior in financial markets. IMF Staff Papers, 47(3), 279310.Bodie, Z., Kane, A., & Marcus, A. J. (2009). Investments (8th ed.). Singapore: McGraw- Hill.Chang, E.C., Cheng, J.W., Khorana, A. (2000). An examination of herd behavior in equity markets: An international perspective. Journal of Banking and Finance, 24(10), 1651–1679.Christie, W.G. dan Huang, R.D. (1995), Following the pied piper: do individual returns herd around the market?. Financial Analysts Journal, 51(4), 31-37.Davino, C., Furno, M. & Vistoco, D. (2014). Quantile regression theory and applications. John Wiley & Sons, Ltd.Filip, A., Pochea, M. and Pece, A. (2015), The herding behaviour of investors in the CEE stock markets. Procedia Economics and Finance, 32, 307-315.Froot, K. A., Scharfstein, D. S., & Stein, J. C. (1992). Herd on the street: informational inefficiencies in a market with short-term speculation. Journal of Finance, 47(4), 1461-1484.Gamage, & Thursari. (2016). Herding in Colombo stock exchange. EFRA International Journal Of Multidisciplinary Research (IJMR), 2, 182-186.Gleason, K., Mathur, I. & Peterson, M. (2004). Analysis of intraday herding behavior among the sector ETFs. Journal of Empirical Finance, 11(5), 681–694.Gunawan, Hari Wijayanto, Noer A. Achsani, La Ode Abdul rahman. (2011). Pendeteksian perilaku herding pada pasar saham Indonesia dan Asia Pasifik. Forum Statistika dan Komputasi, 16(2), 16-23.Hwang S dan Salmon M. 2004. Market stress and herding. Journal of Empirical Finance, 11(4), 585-616.Koenker, R.W., & Bassett, G., Jr. (1978). Regression quantiles. Econometrica, 46(1), 33-50.Koenker, R. (2004). Quantil regression for longitudinal data. Journal of Multivariate Analysis, Elsevier, 91(1), 74-89. Laih, & Yung. (2013). Herding behavior during the suprime mortgage crisis: Evidence from six asia-pasifik stock market. International Journal of Economics and Finance, 5(7), 71-84Lan, Qing Qing and Lai, Rose Neng. (2011). Herding and trading volume. Journal of Finance and Business Economics, SSRN, 1914208, 1-40. Lao, P. & Singh, H. (2011). Herding behavior in the Chinese and Indian stock markets. Journal of Asian Economics, 22(6), 495-528.Malik, Saif Ullah & Elahi, Muhammad Ather, (2014). Analysis of herd behavior using quantile regression: Evidence from Karawachi stock exchange (KSE). MPRA Paper 55322, University Library of Munich, Germany.Ohlson, P. (2010). Herd behavior on the Swedish stock exchange. Master Thesis in Finance. Jonkoping International Business School, Jonkoping University.Ramadhan, T., & Mahfud, M.K. (2016). Deteksi perilaku herding pada pasar saham Indonesia & Singapura Tahun 2011-2015. Diponegoro Journal of Management, 5(12), 96-104. Saastamoinen, Jani. (2008). Quantile regression analysis of dispersion of stock returns-evidence of herding?. Keskustelualoitteita, 57, 1-19.